FORMULATION AND EVALUATION OF SELF-EMULSIFYING DRUG DELIVERY SYSTEM OF ETORICOXIB - Saurabh, Surendra Singh; Issarani, Roshan; Bp, Nagori (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In the present dissertation work, the aim was to prepare self-emulsifying drug delivery systems (SEDDS) of etoricoxib to improve its solubility with a view to enhance its oral bioavailability. Methods: The prepared SEDDS was the concentrate of drug, oil, surfactants, and cosurfactant. The formulation was evaluated for various tests such as solubility, globule size, thermodynamic stability study, pH determination, ease of dispersibility, uniformity index, drug content, in-vitro release study, and in-vitro permeation study. Results: The optimized formulation F6 showed drug release (79.21Â±2.73%), droplet size (0.546 Î¼m). In vitro drug release of the F6 was highly significant (p<0.05) as compared to the plain drug. Conclusion: All formulations of etoricoxib SEDDS were showed faster dissolution than plain drug (p<0.05), mean bioavailability of etoricoxib increase in respect to the plain drug. The F6 can be further used for the preparation of various solid SEDDS formulations.